2019
DOI: 10.1002/ctpp.201800173
|View full text |Cite
|
Sign up to set email alerts
|

Metastable molecular fluid hydrogen at high pressures

Abstract: Warm dense hydrogen is studied in the region of fluid-fluid phase transition within the framework of the density functional theory. We report a procedure of obtaining metastable states and calculate the equation of state. Metastable states are diagnosed by pair correlation functions and values of conductivity. We obtain a strong overlapping through the density of metastable and equilibrium branches of pressure isotherms. This indicates the plasma nature of the phase transition. KEYWORDS density functional theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
(98 reference statements)
1
4
0
Order By: Relevance
“…Therefore the transition between two molecular phases can be envisaged: between the fluid of molecules in the ground state and the growing fluid clusters of excited molecules. This that can qualitatively explain results of 49 . Thus the concept of the plasma phase transition [51][52][53] should be probably reserved for the transition at ultrahigh temperature as has been suggested recently after careful equilibrium analysis of this IMT 18 .…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Therefore the transition between two molecular phases can be envisaged: between the fluid of molecules in the ground state and the growing fluid clusters of excited molecules. This that can qualitatively explain results of 49 . Thus the concept of the plasma phase transition [51][52][53] should be probably reserved for the transition at ultrahigh temperature as has been suggested recently after careful equilibrium analysis of this IMT 18 .…”
supporting
confidence: 77%
“…Recently, the intriguing results have been published that reveal metastable states in fluid H 2 49 . The nature of these metastable states is not clear since they were found using the equilibrium FT-DFT approach.…”
mentioning
confidence: 99%
“…[23,37,38] Later, the insulator-to-metal transition concept has become widespread. [39] The most common approaches are the first principles molecular dynamics (FPMD) based on density functional theory (DFT) [40][41][42][43][44][45][46][47][48][49][50] and quantum Monte Carlo methods. [51][52][53][54][55][56][57][58][59][60] At the same time, the plethora of methods cannot fully explain the key properties of the transition, such as a large isotope effect, [21] a large latent heat of transition, [61] as well as the observed differences in the moments of the detected increase in absorption and reflectivity.…”
Section: Introductionmentioning
confidence: 99%
“…This DFT model contrasts with the finite temperature (FT) DFT method that is used routinely for warm dense fluid H 2 calculations. [42,[44][45][46][47][48][49] Our previous study of the non-adiabatic dynamics of individual electronic excitations [62] showed the possibility of the appearance of localized excitons during the plasma phase transition (excitons in liquids are not unusual, e. g. these states were discovered in liquid Xe). [73,74] The lifetimes of such excitons in fluid H 2 turned out to be of the order of 10 fs, which is much larger than a typical time step in FPMD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation